Students’ Perception On The Implementation Of Intensive English Course For Freshmen At Universitas Indonesia Timur: A Program Evaluation - Nur, Ridwan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
This research was aimed at identifying students’ perception on the implementation of IEC at UIT, to evaluate the program based on the students’ perception and to find out the virtues and weaknesses found during the implementation of the program from the five aspects namely materials, teaching techniques, time allocation, language use, and the importance of the program.This research employed a descriptive survey method. The population of this research was the first semester students of Health Analyst Department, Midwifery Department, and Nursing Department. One class was chosen from each department. There were sixty students as the sample of the research. They were given questionnaire at the end of the semester. They were also interviewed in relation to the implementation of intensive English course. The researcher also took some documentations to gain the supporting data. Based on the findings and discussion, all the students perceived that the intensive English course is a very good and important program to develop their communication ability especially their English language skill. From the aspect of materials, the students stated that the materials were good and appropriate to their English needs as health department students but some stated that the materials were difficult to understand and memorized. From the aspect of teaching technique, the students stated that they liked to be taught by different instructors because they provided different ways of teaching and they were nice and funny so it makes the class more enjoyable and comfortable. Some students stated that not all the instructors were good in delivering the materials. Also there was an instructor who always uses the same technique in every meeting and there was no variation, so they feel boring to study. From the aspect of time allocation, the students thought that five meetings in a week are enough and effective for them but many of them thought that an hour in a meeting is not enough to study moreover if the instructors came late. From the aspect of language use, the students stated that they always tried to use English when they wanted to speak to their friends and foreigners and they always active in every activity in the classroom like in discussion and ask a question. The others said that they could not speak English well because they did not have sufficient vocabularies and they did not understand how to translate English sentences into Indonesian. From the aspect of the importance of the program, all students concluded that the program was very important to develop their communication ability for their future with various reasons